CHANGES IN MAGNETIC PROPERTIES OF BAKED ARCHAEOLOGICAL SAMPLES. IMPLICATIONS FOR PALAEOINTENSITY DETERMINATION - Jordanova N.; Jordanova D.; Petrovsky E.; Kovacheva M. (My University, 2001)
Rock magnetic investigations of archaeological materials of burnt clay from Eneolithic ovens (~4500 years BC) showed particular changes with time in the magnetic mineralogy of samples, stored under normal conditions. Our results indicate that well-burnt clay from the archaeological materials contains a significant amount of very fine magnetic grains, which could notably influence the rock magnetic properties and behavior at room temperature. The main observations after 4 years of storage under laboratory conditions are as follows: 1) decrease in the final unblocking temperature of NRM from ~600-620°C to ~580°C and 2) increase in the capacity of laboratory TRM acquisition. The most probable mechanism responsible for the observed changes is supposed to be fast low-temperature oxidation of the finest (superparamagnetic) grains and the development of the maghemite shell in coarser single-domain grains. The Thellier palaeointensity experiments, carried out at the beginning of the study, showed very good results, which satisfy all acceptance criteria, applied to evaluation of the results, quite well. Palaeointensity determinations repeated 4 years later on samples from the same material showed the experimental results to be of significantly inferior quality. The main difference is the presence of the significant deviation (change in the slope) on the Arai diagram after T>350-400°C. The calculated palaeointensity is either higher than the one obtained before, or similar, but evaluated with large uncertainty. Therefore, we conclude that the possibility to obtain biased palaeointensity values increases during short-time storage (i.e. several years) due to the low-temperature changes of the material.
Keywords: BURNT CLAY; LOW-TEMPERATURE OXIDATION; ARCHAEOINTENSITY; MAGNETITE